Emotional Support of Husband with Primigravida Pregnant Women's Anxiety Level in Childbirth at RSU Imelda Pekerja Indonesia - Gultom, Risa Tantry (SEAN Institute, 2023)
Primigravida mothers generally have difficulty detecting changes in their bodies that cause discomfort during pregnancy. Your husband's support during her pregnancy will help her feel safe and at ease. The goal is to determine the emotional support of husbands with the level of anxiety of Primigravida pregnant women in the delivery process at RSU Imelda Pekerja Indonesia. In this study, it showed that the majority of mothers did not get the support of their husbands, namely 24 (43%). The anxiety level of pregnant women is mostly moderate anxiety, which is 22 (52%). Based on the chi sqaure test, a p value = 0.003 was obtained, so it can be concluded that there is a significant relationship between demotional support sumai and the level of anxiety of pregnant women Primigravida in labor. There is a significant relationship between the emotional support of the husband and the level of anxiety of pregnant women when facing childbirth. Mothers who give birth comfortably and calmly will reduce the occurrence of anxiety during labor.